Konsep Dakwah Nabi Nuh Dalam Kitab Tafsir Al-Qurtubi Karya Abu Abdullah Muhammad - Moh. Muafi Bin Thohir; Muhammad Abdul Halim Sidiq (Institut Agama Islam Syarifuddin Lumajang, 2021)
Da'wah is an activity of invitations, calls, and also the process of influencing someone to change from one condition to another desired condition. This study choses the da'wah of the Prophet Nu to be the subject of its study, due to the length of the da'wah period and the severity of the obstacles faced by the Prophet Nuh. He has a concept of da'wah which is effective and ideal to do, it is explained by Allah in the Qur'an, Surah Nuh. Prophet Nuh had gone through the toughest challenges of his people with great patience. This research focuses on explaining how the concept of da'wah the Prophet Nuh in the book Tafsir Al-Qurtubi by Abu Abdullah Muhammad. This research is also a thematic exegesis research. Therefore, this study was prepared using the thematic interpretation method or maudu'i which was initiated by Abd Al-Hayy Al-Farmawi. The results of this study are an explanation of the interpretation of verses about the concept of the Prophet Nuh, including Surah Hud: 29, Surah Nuh: 1- 3,5,8-9,28. Then the explanation of the concept of da'wah the Prophet Nuh which has three components of da'wah, among others, the method of da'wah, the content of the message and the purpose of the da'wah as well as an explanation of its realization in today's life. Keywords: Al-Qurtubi, Da'wah, Prophet Nuh, Thematic